2019
DOI: 10.1103/physreve.100.052102
|View full text |Cite
|
Sign up to set email alerts
|

Nonintegrability and thermalization of one-dimensional diatomic lattices

Abstract: Nonintegrability is a necessary condition for the thermalization of a generic Hamiltonian system. In practice, the integrability can be broken in various ways. As illustrating examples, we numerically studied the thermalization behaviors of two types of one-dimensional (1D) diatomic chains in the thermodynamic limit. One chain was the diatomic Toda chain whose nonintegrability was introduced by unequal masses. The other chain was the diatomic Fermi-Pasta-Ulam-Tsingou-β chain whose nonintegrability was introduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 45 publications
8
36
1
Order By: Relevance
“…Some years later, it has been given the evidence that, in the large box limit, the mechanism that leads to the thermalization in chains like the α-and β-FPUT is the four-wave resonant interaction process [4,5], see also [6]. Numerical confirmation of these predictions can be also found in [7,8].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some years later, it has been given the evidence that, in the large box limit, the mechanism that leads to the thermalization in chains like the α-and β-FPUT is the four-wave resonant interaction process [4,5], see also [6]. Numerical confirmation of these predictions can be also found in [7,8].…”
Section: Introductionmentioning
confidence: 93%
“…a diatomic chain with cubic potential (quadratic nonlinearities in the equation of motion) and we study the properties of thermalization within the wave turbulence framework [9,10]. Numerical simulations of a diatomic β-FPUT chain and of the diatomic Toda lattice were considered in [11] and it was shown that the thermalization time followed the same scaling as the one for monoatomic chains α-and β-FPUT [5,12] and the nonlinear Klein-Gordon equation [13]. From a mathematical point of view, we point out a rigorous result in [14] for a diatomic chain where it was proved that, in the limit of small temperature and large ratio between the masses, the exchange of energy between the modes of the optical branch and those of the acoustic one is practically null for the majority of initial conditions up to some time estimated in [14] (see also [15,16]).…”
Section: Introductionmentioning
confidence: 99%
“…At lower energies, one should estimate the soliton scattering rates due to mass inhomogeneities; however, there is no reason to expect a different scaling behavior. Indeed, the typical thermalization time is of order δ −2 in a wide energy range [64]. The conductivities taken from Ref.…”
mentioning
confidence: 99%
“…The form and the strength of H ′ completely depend on the choice of H 0 . And the existing research results show that the choice of H 0 is very important to characterize the thermalization behavior of a system [22,24,31].…”
Section: The Modelsmentioning
confidence: 99%
“…Recent studies have shown that these scaling laws can be explained in the framework of wave turbulence theory [18][19][20]. Subsequently, it is shown that, in the thermodynamic limit, the thermalization behavior of a near-integrable system is universal as long as the ability of the system to be thermalized is properly measured, that is, the T eq is inversely proportional to the square of the perturbation strength [21][22][23][24][25][26]. The key to accurately describing the thermalization capability of a system is to define the perturbation strength by selecting a suitable reference integrable system [22].…”
Section: Introductionmentioning
confidence: 99%